Identification of Dendritic Cell Maturation, TLR, and TREM1 Signaling Pathways in the Brucella canis Infected Canine Macrophage Cells, DH82, Through Transcriptomic Analysis - Park, Woo Bin; Kim, Suji; Shim, Soojin; Yoo, Han Sang (Frontiers in Veterinary Science, 2021)
Research has been undertaken to understand the host immune response of Brucella canis infection because of the importance of the disease in both the public-health and clinical fields. However, the previous mechanisms governing this infection have not been elucidated. Therefore, in vitro models, which mimic the in vivo infection route using a canine epithelial cell line, D17, and a canine macrophage, DH82, were established to determine these mechanisms by analysis of the transcriptomes in the cells. In this study, a co-culture model was constructed using the D17 and DH82 cell lines in the trans-well plate. Also, a single cell line culture system using DH82 was used. After stimulation of the cells in two different systems with B. canis, gene expression in the macrophages of the two different systems was analyzed by RNA-seq, and transcriptomic analysis was performed by Ingenuity Pathway Analysis. Gene expression patterns were analyzed in DH82 cell line at 2, 12, and 24 hours after stimulation with B. canis. Up- or down-regulated genes showing 2-fold changes or higher were identified at each time points by comparison with non-stimulated group. DEGs (Differentially expressed genes) between the two culture models were identified using IPA program. Generally, the number of genes expressed in the single cell line culture was higher than that in the co-culture model at all-time points. The expression levels of those genes were higher in the single cell line culture (p<0.05). This analysis indicated that pathways related to immune-responses, especially, dendritic cell maturation, TREM1 signaling, and the TLR signaling pathway were significantly induced in both culture systems with higher p-values and z-scores. Increase in the expression level of genes related with the pathways was observed over time. All pathways are commonly associated with the manifestation of pro-inflammatory cytokines and early immune responses. However, PPAR signaling and LXR/RXR signaling associated with lipid metabolism were reduced. These results indicate that early immune responses might be highly activated in B. canis infection. Therefore, these results might suggest clues to reveal the early immune response of the canine to B. canis infection, especially TLR signaling.